Chemotaxis detection towards chlorophenols using video processing analysis - Okada, Elena (2017)
To our knowledge, this communication is the first report of chemotaxis towards chlorophenols by any bacteria. We used a recently published method based on the agarose in-plug assay combined with video processing analysis and we also present a new index of bacterial mean speed for these assays.